Indonesian Ministry of Tourism and Creative Economy promotion strategy during the covid-19 pandemic - Dicky Herdyawan Bachrudin; Safendrri Ragamustari (Jurnal Pariwisata Pesona, 2023)
The COVID-19 pandemic that has occurred throughout the world has caused enormous damage to the world economy, including Indonesia. The Indonesian tourism industry has suffered heavy losses due to restrictions on travel, both domestically and internationally, and the prohibition of mass gatherings. During the pandemic, a series of new policies and rules were made to prevent the transmission of the virus. At the same time, there was an increase in the use of gadgets, social media, and the internet, which caused doubt, fear, and uncertainty for tourists to travel as negative news spreads. Tourism has a negative image that must be improved through a series of innovative programs that provide tourists with health concerns to lower the risk of transmission. Through social media, tourism industry must be keen to see opportunities to bounce back through a series of promotional strategies and innovations in carrying out 'New Normal.' Using descriptive qualitative methods and data triangulation process from an interview, observation, and document analysis, this paper will discuss a series of techniques carried out by Indonesia Ministry Of Tourism and Creative Economy (IMOTCE) during the COVID-19 pandemic. The result found that during pandemic, IMOTCE had multiple key-message delivered through YouTube video in Pesona Indonesia. These key-messages were based on situation and government policy in order to stop COVID-19 outbreak.